2023
DOI: 10.2147/ijgm.s425992
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Aflatoxin B1 Exposure to Liver Cirrhosis in Eastern Ethiopia: A Case-Control Study

Abstract: Background Liver cirrhosis is a global health problem due to a large number of disability-associated life years and mortality. However, evidence is scarce on its causes in Eastern-Ethiopia, a place where there is a high prevalence of liver cirrhosis of unknown etiology. This study attempted to identify the risk factors related to liver cirrhosis in the area. Methods A case-control study was conducted at a tertiary care hospital from January 2020 to July 2021. Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“… 33–35 Indeed, in our recent study, HBV infection and AFB 1 exposure were the major culprits of liver cirrhosis in Eastern Ethiopia. 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 33–35 Indeed, in our recent study, HBV infection and AFB 1 exposure were the major culprits of liver cirrhosis in Eastern Ethiopia. 9 …”
Section: Discussionmentioning
confidence: 99%
“…This is a follow-up of a case–control study conducted from January 2020 – July 2021 to assess the risk factors associated with liver cirrhosis in the Internal Medicine Unit of Hiwot Fana Comprehensive Specialized University Hospital (HFCSUH), Harar, Eastern Ethiopia. 9 In brief, the study consisted of 127 confirmed cases of liver cirrhosis and 253 controls without any history or clinical evidence of liver diseases. Written consent from the participants was obtained after explaining aims of the study and a detailed questionnaire was filled out for each case and control by a trained interviewer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is part of a study conducted in a tertiary hospital in Harar, Eastern Ethiopia, to explore risk factors for liver cirrhosis from 1 January 2020 to 31 July 2021. 7 In short, the study included 253 controls who had no history of liver disease and 127 verified instances of hepatic cirrhosis. After explaining the study's objectives to the participants', written consent was obtained, and a professional interviewer completed a thorough questionnaire for each case and control.…”
Section: Study Setting and Subjectsmentioning
confidence: 99%
“…In this regard, our recent case-control study found aflatoxin B 1 (AFB 1 ) exposure as a potential missing etiologic factor of liver cirrhosis in Eastern Ethiopia, where significant cases of the disease were cryptogenic. 7 Thus, it is imperative to explore the potential predictive factors for the unknown etiology of liver cirrhosis to obtain clues for further missing etiologies and for potential sources of exposure to AFB 1 and its predictors. Hence, this study aimed to identify the possible sociodemographic, dietary, lifestyle, and clinical factors associated with the unknown etiology of liver cirrhosis in Eastern Ethiopia.…”
Section: Introductionmentioning
confidence: 99%